INTERKULTURALISME DARI NASKAH DRAMA TERJEMAHAN KE SADURAN - Lina Meilinawati Rahayu (LITERASI: Indonesian Journal of Humanities, 2011)
This article discusses interculturalism in an adapted drama text. The text under consideration here is Jembangan yang Pecah, adapted by Suyatna Anirun from Der Zerbrochene Krug by Heinrich von Kleist. Translation is a kind of transformation process. In the process there is an effort to adapt the text with the held performance. The process from original text to translation text is one of the concerns of interculturalism idea. An Idea constitutes a development of multiculturalism adaptation. During the performance, the audience will arrive at their interpretation in a brief moment whereas adapting a text from a different language and culture demands special efforts in the process of interpretation. The successful performance of adapted texts has also indicated that adapted texts are easier to perform because they -in comparison to Indonesian original texts- show more conformity to the required dramatic structures. Keywords: interculturalism, adaptation, transformation